Self-administration of the synthetic cathinone MDPV enhances reward function via a nicotinic receptor dependent mechanism. (15th July 2018) - Geste, Jean R.; Pompilus, Marjory; Febo, Marcelo; Bruijnzeel, Adriaan W.
Abstract: Methylenedioxypyrovalerone (MDPV) is an addictive synthetic drug with severe side effects. Previous studies have shown that MDPV has positive reinforcing properties. However, little is known about the effect of MDPV self-administration on the state of the brain reward system and the neuronal mechanisms by which MDPV mediates its effects. The goal of the present studies was to determine the effect of MDPV self-administration on reward function and the role of cholinergic neurotransmission in the reinforcing effects of MDPV. To study the effect of MDPV self-administration on the brain reward system, rats were prepared with intravenous catheters and intracranial self-stimulation electrodes (ICSS). For 10 days, the reward thresholds were assessed immediately before (23 h post prior session) and after 1 h of MDPV self-administration. The reward thresholds were decreased immediately after MDPV self-administration, which is indicative of a potentiation of brain reward function. The reward thresholds 23 h after MDPV intake gradually increased over time, which is indicative of anhedonia. Pretreatment with the nicotinic acetylcholine receptor (nAChR) antagonist mecamylamine decreased the self-administration of MDPV and completely prevented the decrease in reward thresholds. A control study with palatable chocolate pellets showed that responding for a natural reinforcer does not affect the state of the brain reward system. Furthermore, mecamylamine did not affect responding for food pellets. In conclusion, the self-administration of MDPV potentiates reward function and nAChR blockade prevents the reward enhancing effects of MDPV self-administration. Preventing the MDPV-induced increase in cholinergic neurotransmission might be a safe approach to diminish MDPV abuse. Highlights: MDPV self-administration potentiates brain reward function in rats. Blockade of nAChRs decreases MDPV self-administration. Blockade of nAChRs diminishes reward enhancing effect of MDPV self-administration. Operant responding for palatable food pellets does not affect reward function. Blockade of nAChRs does not affect operant responding for palatable food pellets.